Low-Energy Signatures of Semi-perturbative Unification - Kolda, C; March-Russell, J (1996)
We consider the low-energy signatures of, and high-energy motivations for, scenarios of semi-perturbative gauge coupling unification. Such scenarios can leave striking imprints on the low-energy sparticle spectrum, including novel gaugino mass ratios (including $M_2/M_1≈1$), substantial compression of the intra-generational squark-to-slepton mass ratios, and an overall lifting of scalar masses relative to the gauginos. We also demonstrate that the unification scale can be raised to $M_X ≈ 4×10^{17}$ GeV while still in the perturbative regime -- close to the 1-loop heterotic string scale. We employ a 3-loop calculation of the running of the gauge couplings as a test of the perturbativity of the high-scale theory.